Course of pregnancy and 10-year observation of twins diagnosed with GCK-MODY in the neonatal period: a case report - Katra, Barbara; Szopa, Magdalena (Frontiers in Endocrinology, 2024)
Monogenic diabetes accounts for 5% of all incidence of hyperglycemia and Maturity Onset Diabetes of the Young (MODY) is it's the most common form. In GCK-MODY, one of the most common forms of MODY, hyperglycemia is caused by a mutation of a gene responsible for coding glucokinase. At the clinical level, this condition presents as persistent, moderate and asymptomatic elevated fasting glucose levels and has a relatively low incidence of micro and macro-vascular complications. In general, the treatment of choice is to follow and maintain a healthy lifestyle. The incidence of GCK-MODY during pregnancy is 2% on average (0-6%). In this report, we introduce a case of a woman diagnosed with GCK-MODY during the pregnancy with twins, a boy and a girl, diagnosed with GCK-MODY after birth. We discuss the course of pregnancy, the need for access to fast and uncomplicated genetic diagnostics in utero, and the impact of the MODY diagnosis on the life of the mother and that of her children. In our case, the diagnosis of GCK-MODY was associated with a feeling of relief, after years of uncertainty, and helped to introduce more appropriate eating behaviors and lifestyle changes for both the mother and her children.